Multicultural-Based Learning of Al Islam Kemuhammadiyahan in Muhammadiyah Universities: Uniting Science and Tolerance in Progress: Pembelajaran Al Islam kemuhammadiyahan Berbasis Multikultural di Perguruan Tinggi Muhammadiyah: Menyatukan Ilmu dan Toleransi berkemajuan - Amrullah, Muhlasin; Astutik, Anita Puji; Hikmah, Khizanatul (Procedia of Social Sciences and Humanities, 2024)
The significance of Al Islam Kemuhammadiyahan education within Indonesian higher education is underscored by Muhammadiyah's commitment to integrating Islamic principles with contemporary educational needs. This approach is vital in addressing the growing complexities of a multicultural society.Muhammadiyah, founded in 1912 by KH Ahmad Dahlan, emphasizes a moderate and progressive Islamic education that combines academic excellence with moral development. This educational model is designed to foster individuals who are both intellectually competent and ethically grounded.Despite extensive documentation on Muhammadiyah's educational principles, there is limited empirical research on how these principles are effectively applied in multicultural settings within higher education institutions.This study employs a qualitative case study approach to explore the implementation of multicultural-based Al Islam Kemuhammadiyahan education at Muhammadiyah higher education institutions. It aims to analyze how these institutions integrate Islamic values with multicultural principles in their educational practices.